PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN USAHA IKAN ASIN DI KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Beryaldi Agam; Nurul Eka Wijayanti Risa; Andi Panca Wahyuni (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2022)
The excess unsold fish catches are used by fishermen's wives to increase income by processing them into salted fish. The purpose of this study is to determine the influence of socioeconomic factors on the income of salted fish businesses. The research was carried out from April to May 2022 located in Penjajap Village, Pemangkat District, Sambas Regency. This research is a quantitative descriptive study using multiple linear analysis methods using SPSS 26 software. The results showed that 1). Socioeconomic factors such as the level of education, the number of dependents, the length of business, and the number of workers partially (partially) affect the income of salted fish entrepreneurs while the socioeconomic factors of age do not affect the income of salted fish entrepreneurs in Pemangkat District, Sambas Regency; 2). Socioeconomic factors such as age, level of education, number of dependents, length of business, and the number of workers together (simultaneously) affect the income of salted fish entrepreneurs in Pemangkat District, Sambas Regency.